6 - An exploration of the philosophy and environment of a South African randomized, double-blind, placebo-controlled trial of Lessertia frutescens - Olajide Oloyede (African Sociological Review, 2011)
The current paper describes the context setting that was undertaken when designing and conducting the first pilot study of the safety of Sutherlandia (lessertia frutescences), a plant indigenous to South Africa which is generally used, in the country, as a traditional medicine in the treatment of a number of illnesses, including symptoms associated with hiv/AiDS. it asks: Do the researchers who conducted the clinical trial consider the rationale broadly, profoundly and objectively enough? it examines how and why the context setting was undertaken and highlights important aspects of the culture and organization of the clinical trial which might have influenced the participants’ experiences in trial recruitment and participation. The gen- eral aim is to build a picture of the environment in which clinical trials were offered and administered. This is because properly conducted clinical trials are key to the knowledge needed by health care bodies to deliver effective, safe and economically sound treatment. The focus is on the organization of the work of the institute that conducted the clinical trial, the place of trials work within the institute and the beliefs, attitudes and practices of the staff.